A comparative study on the bottleneck flow between preschool children and adults under different movement motivations. (January 2020) - Li, Hongliu; Zhang, Jun; Yang, Libing; Song, Weiguo; Yuen, Kwok Kit Richard
Highlights: We analyze bottleneck flow of preschool children in a laboratory experiment. The pedestrian flows of children and adults under different movement motivations are compared. The relations between flow and bottleneck width for children and adults are unified. Arch-like and teardrop-shape distributions are observed for the children' and adults' movement respectively. Abstract: Understanding on children's movement characteristics is significant to improve their safety levels especially under emergencies. In this work, we perform laboratory experiment to investigate the dynamics of preschool children aged 3–5 years old passing through normal bottlenecks of different widths under high movement motivation. Trajectories of children are extracted automatically and Voronoi Diagram based methods are used to calculated the density, velocity and other parameters. It is found that the relations between flow and bottleneck width for adults and children can be unified when the body size and movement motivation are considered in certain way. High movement motivation leads to competition among pedestrians, which results in different spatial-temporal distribution of the density and speed compared to normal movement of adults. An arch-like distribution is observed for the children movement with competition, whereas it is teardrop-shaped for the adults without competition. The locations of the peak density lie around 0.3 m from the bottleneck entrance in this study with the bottleneck width changing from 0.4 m to 1.0 m, while for adults, the location of the peak density region is about 1.0 m with the bottleneck width changing from 0.9 m to 1.1 m. Besides, several typical behaviors of children are observed in the experiment, like guiding, pushing as well as playing. The results can help researchers understand the movement dynamics of preschool children.